2008
DOI: 10.1016/j.cognition.2007.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Attention capture by faces

Abstract: We report three experiments that investigate whether faces are capable of capturing attention when in competition with other non-face objects. In Experiment 1a participants took longer to decide that an array of objects contained a butterfly target when a face appeared as one of the distracting items than when the face did not appear in the array. This irrelevant face effect was eliminated when the items in the arrays were inverted in Experiment 1b ruling out an explanation based on some low-level image-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
261
7
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(303 citation statements)
references
References 37 publications
24
261
7
1
Order By: Relevance
“…Further examination of the target present trials revealed that participants were quicker to reject displays in which the distracters are faces than when they are non-face distracter displays. This indicates that participants are (1) faster to detect faces than nonsocial images, as targets and (2) The finding that both ASD and TD participants in this study were faster to find nonsocial targets in face fields than in other non-social fields contradicts the findings of Langton et al (2008) and Riby et al (2012). In these two previous studies participants were slower to find a non-face target (a butterfly) when the distractor field included the image of a face.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Further examination of the target present trials revealed that participants were quicker to reject displays in which the distracters are faces than when they are non-face distracter displays. This indicates that participants are (1) faster to detect faces than nonsocial images, as targets and (2) The finding that both ASD and TD participants in this study were faster to find nonsocial targets in face fields than in other non-social fields contradicts the findings of Langton et al (2008) and Riby et al (2012). In these two previous studies participants were slower to find a non-face target (a butterfly) when the distractor field included the image of a face.…”
Section: Discussioncontrasting
confidence: 55%
“…Others have also examined how faces may capture attention when they are not the targets in cognitive-behavioural tasks. Langton et al (2008) asked TD participants to detect the presence or absence of butterfly targets in a visual search task. On 50% of trials an irrelevant face distractor was included.…”
Section: Introductionmentioning
confidence: 99%
“…While the effect of inversion is not significant for normal faces, the direction of the difference is the same, with search among inverted faces being faster. This is consistent with upright faces also grabbing attention, as found by Langton et al (2008), who report a 20ms effect of inversion, comparable with the 28ms found here. The search times per item for both normal and double faces when inverted are essentially identical.…”
Section: Resultssupporting
confidence: 81%
“…That is, an IOR response is still expected to occur at the 150 ms SOA, but overall RTs should be faster for face trials compared to house trials, regardless of cued or uncued positions. Since faces should initially capture a faster shift of attention compared to houses (Bindemann et al, 2005;Langton et al, 2008;Palermo & Rhodes, 2007;Ro et al, 2001), it is then predicted that at the later SOAs, a greater IOR response should be seen for faces in general compared to houses. Since faces can capture attention very rapidly, at around~100 ms (Crouzet et al, 2010), and should be processed in depth very quickly (Langton et al, 2008;Ro et al, 2001), there should not be a need to immediately re-examine a face once it has been attended to because vital social information (like eye gaze) should have been fully processed from the initial attention capture.…”
Section: Introductionmentioning
confidence: 99%
“…In these paradigms, both types of stimuli should capture attention and lead to an IOR response. However, faces should initially capture more reflexive attention compared to other stimuli (Bindemann et al, 2005;Langton et al, 2008;Palermo & Rhodes, 2007;Ro et al, 2001) since faces are processed faster and more in depth than other stimuli. This means that after attention is disengaged from the stimulus cue (and brought back to fixation), there should be a stronger inhibition to return to that previously attended area where the face was, compared to if another stimulus was there, since the faces were more thoroughly attended to, and there should be a stronger bias to search for novel locations (perhaps for new faces).…”
Section: Introductionmentioning
confidence: 99%